MOTIVASI DAN KINERJA - Jurica Lucyanda (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2007)
The role of motivational processes in determining a worker’s level performance is now widely recognized by industrial psychologists. Viteles (1953) has identified the development of the ’’will to work" as industry’s core problem in the utilization of its manpower; Maier (1955) indicates the need for greater attention to problems of motivation and frustration by industrial firms. The objective of this paper is to explain the nature of the relationship between motivation and performance. Hence, the more motivated the worker to performance effectively, the more effective his or her performance.